PEMBELAJARAN BAHASA INGGRIS MENULIS NARRATIVE DI PADLET DAN BERBICARA DENGAN TALK SHOW - Erna Pujiasih (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
Narrative with talk shows aims to apply the ability of learners to write narrative stories and present with talk shows. This method uses descriptive qualitative . Data is obtained based on observation, implementation of learning and questionnaires. The subject of this study were students of Class XI SMA Negeri 1 Bantul. Based on the best practices in the learning was done by the explanation of the material Narrative group activities in writing and speaking with talk shows. Based on the results of the questionnaire and the practice of writing stories and the talk show, learners can write stories, practical writing in Padlet, creative, fun, experience, increase grammar and vocabulary, have self confidence , improve speaking skills, work together and tell each other with relax.